How can biomolecules improve mucoadhesion of oral insulin? A comprehensive insight using ex-vivo, in silico and in vivo models - Amaral, Mariana (2020)
Currently, insulin can only be administered through the subcutaneous route. Due to the flaws associated with this route, it is of interest to orally deliver this drug. However, insulin delivered orally has several barriers to overcome as it is degraded by the stomach’s low pH, enzymatic content, and poor absorption in the gastrointestinal tract. Polymers with marine source like chitosan are commonly used in nanotechnology and drug delivery due to their biocompatibility and special features. This work focuses on the preparation and characterization of mucoadhesive insulin-loaded polymeric nanoparticles. Results showed a suitable mean size for oral administration (<600 nm by dynamic laser scattering), spherical shape, encapsulation efficiency (59.8%), and high recovery yield (80.6%). Circular dichroism spectroscopy demonstrated that protein retained its secondary structure after encapsulation. Moreover, the mucoadhesive potential of the nanoparticles was assessed in silico and the results, corroborated with ex-vivo experiments, showed that using chitosan strongly increases mucoadhesion. Besides, in vitro and in vivo safety assessment of the final formulation were performed, showing no toxicity. Lastly, the insulin-loaded nanoparticles were effective in reducing diabetic rats’ glycemia. Overall, the coating of insulin-loaded nanoparticles with chitosan represents a potentially safe and promising approach to protect insulin and enhance peroral delivery.